2015
DOI: 10.1155/2015/192383
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Shock Emission in Gamma-Ray Bursts Revisited

Abstract: A generic synchrotron external shock model is the widely preferred paradigm used to interpret the broadband afterglow data of gamma-ray bursts (GRBs), including predicted observable signatures from a reverse shock which have been confirmed by observations. Investigations of the nature of the reverse shock emission can provide valuable insights into the intrinsic properties of the GRB ejecta. Here we briefly review the standard and the extended models of the reverse shock emission, discussing the connection bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 160 publications
(226 reference statements)
0
10
0
Order By: Relevance
“…Notwithstanding the constraints on t 0 , our revised decay indices of the Xray fluxes are still too steep ( 2) with respect to the model predictions for the forward shock (1.2, assuming that the energy distribution of the accelerated particles has a power-law shape with an index p=2.2, Wang et al 2003). The scenario of a reverse shock that is dominant in X-rays has been considered to explain some GRBs' afterglows (see Gao & Mészáros 2015, for a review). Genet et al (2007) have shown that the X-ray emission from a reverse shock may be dominant during the early afterglow phase provided that: 1-the bulk motion of the material ejected during the last stages of the source activity is Γ bulk <10 and 2-a large part of the shock-dissipated energy is transferred to a small fraction of the electron population (see also Uhm & Beloborodov 2007).…”
Section: Constraints On the Particle Acceleration Process From The Brmentioning
confidence: 87%
“…Notwithstanding the constraints on t 0 , our revised decay indices of the Xray fluxes are still too steep ( 2) with respect to the model predictions for the forward shock (1.2, assuming that the energy distribution of the accelerated particles has a power-law shape with an index p=2.2, Wang et al 2003). The scenario of a reverse shock that is dominant in X-rays has been considered to explain some GRBs' afterglows (see Gao & Mészáros 2015, for a review). Genet et al (2007) have shown that the X-ray emission from a reverse shock may be dominant during the early afterglow phase provided that: 1-the bulk motion of the material ejected during the last stages of the source activity is Γ bulk <10 and 2-a large part of the shock-dissipated energy is transferred to a small fraction of the electron population (see also Uhm & Beloborodov 2007).…”
Section: Constraints On the Particle Acceleration Process From The Brmentioning
confidence: 87%
“…For relativistic RS, one more additional parameter, T 90 , representing the width of the ejected shell, enters the picture. For a detailed review, see Gao & Mészáros (2015). Synchrotron spectrum from the reverse shocked ejecta can be calculated from the properties of the downstream the same way as described for the FS in section-4.2.…”
Section: Reverse Shock Emissionmentioning
confidence: 99%
“…Both the X-ray plateaus and the optical re-brightenings can not be explained in the framework of a simple FS scenario. Thus researchers have proposed several refined models to interpret these unexpected features in recent years (see [21,22] for a review). Stimulated by these refined models, it is urgent to answer whether X-ray plateaus and optical re-brightenings have a natural origin or they are special outcomes varying in different GRBs.…”
Section: Introductionmentioning
confidence: 99%